Red flour beetle survival on different food items - Baghdad Science Journal (مجلة بغداد للعلوم)
Studied red beetle life on each of the yen and wheat durum wheat, barley, corn, rice, chickpeas, ground peanuts and beans in Living situation constant temperature and relative humidity of 65% for a period of 66 days was the life cycle of the insect different from one substance to another ....